2019
DOI: 10.1055/a-0837-0975
|View full text |Cite
|
Sign up to set email alerts
|

Icariin Attenuates High Glucose-Induced Apoptosis, Oxidative Stress, and Inflammation in Human Umbilical Venous Endothelial Cells

Abstract: Endothelial dysfunction is closely associated with diabetic complications. Icariin, a flavonoid glycoside isolated from the Epimedium plant species, exhibits antidiabetic properties. However, its impact on endothelial function remains poorly understood, particularly under hyperglycemia. In this study, we investigated the potential protective effect of icariin on high glucose-induced detrimental effects on vascular endothelial cells. Human umbilical venous endothelial cells were incubated in media containing 5.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 58 publications
1
16
0
Order By: Relevance
“…High glucose treatment was performed as our described previously [29,30]. The control group received the treatment of 5.5 mM glucose and the identical concentration of mannitol which act as osmotic control to remove a hyperosmolar effect.…”
Section: Cell Culture and Treatmentmentioning
confidence: 99%
“…High glucose treatment was performed as our described previously [29,30]. The control group received the treatment of 5.5 mM glucose and the identical concentration of mannitol which act as osmotic control to remove a hyperosmolar effect.…”
Section: Cell Culture and Treatmentmentioning
confidence: 99%
“…High glucose treatment was performed as our described previously [20,21]. The control group received the treatment of 5.5 mM glucose and the identical concentration of mannitol which act as osmotic control to remove a hyperosmolar effect.…”
Section: Cell Culture and Treatmentmentioning
confidence: 99%
“…Effective herbal drugs for treatment of endothelial dysfunction should be able to improve NO synthesis and reduce ROS synthesis and apoptosis induced by deleterious agents such as high concentration of d -glucose or hydrogen peroxide [ 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…The authors found that the polyphenolic compounds in the extract were potent ROS inhibitors, capable of blocking protein glycation, and had an antiapoptotic effect. Recently, it has been determined that icariin, a flavonoid glycoside isolated from the plant species Epimedium , can protect against high d -glucose-induced endothelial dysfunction in vitro, through attenuation of apoptosis, oxidative stress, and inflammation [ 18 ]. In general, HUVECs are considered a reliable and simple in vitro model for predicting and understanding the biological response of endothelial cells to plant extracts.…”
Section: Introductionmentioning
confidence: 99%